Analysis of the aerobic sludge microbial community structure and degradation pathways of diethylene glycol monobutyl ether - GUAN Ying; LIU Run; QIN Pinzhu; ZHANG Ruimin (Gongye shui chuli)
Aerobic biodegradation was employed to degrade Diethylene glycol monobutyl ether(DGBE), and the degradation effect was investigated by gradually increasing the influent DGBE concentration. Activated sludge samples were collected for high-throughput sequencing analysis before, during the stable period, and at high concentration acclimation, respectively. The potential degradation pathways of DGBE were inferred based on the identification of intermediate products. The experimental results indicated that when the DGBE concentration was below 832.85 mg/L, the removal rates of DGBE and COD could achieve over 99% and 93%, respectively, while a further increase in influent concentration led to a decline in removal efficiency. The richness and diversity of the microbial community in the activated sludge were significantly reduced after DGBE acclimation. During the stable acclimation period, the dominant phylum was Proteobacteria(78.59%), with the dominant genera of Cupriavidus(42.44%) and Rhodanobacter(20.02%). In the high concentration acclimation period, Actinobacteriota(51.15%) surpassed Proteobacteria(43.41%) as the most abundant phylum, and Nakamurella(49.81%) was the primary dominant genus. The main intermediate products of DGBE were detected, as butyl glycol, butyraldehyde, and vinyl butyl ether, suggesting possible degradation pathways as the ω-oxidation and β-oxidation pathway, and the ether bond cleavage degradation pathway due to sub-terminal oxidation.